Is immediate weight bearing safe for periprosthetic distal femur fractures treated by locked plating? A feasibility study in 52 consecutive patients. Issue 1 (December 2016) - Smith, Wade; Stoneback, Jason; Morgan, Steven; Stahel, Philip
Abstract Background Periprosthetic distal femur fractures associated with total knee replacement are increasing in incidence. We hypothesized that a standardized management protocol would result in few implant failures and a low rate of postoperative complications. Methods Retrospective observational cohort study at an urban level 1 trauma center and academic level 2 trauma center. Consecutive patients with periprosthetic distal femur fractures and stable total knee arthroplasty were included between January 1, 2011 and December 31, 2014. Patients were managed by a standardized protocol of co-management by a hospitalist service, fracture fixation within 24 h of admission by less-invasive locked bridge plating, and immediate unrestricted postoperative weight bearing. The primary outcome measure was the rate of postoperative complications. Secondary outcome measures included time to surgery, intraoperative blood loss, duration of surgery, length of hospital stay, time to full weight bearing, and time to radiographic fracture healing. Results Fifty four fractures were treated in 52 patients. There were three implant failures, one deep infection, one nonunion and two patients with symptomatic malunion. One patient had knee pain due to patellar component instability associated with valgus alignment. There were ten thromboembolic complications despite consistent anticoagulation. Two patients died within 12 months of injury. Thirty-eight patients had returned to their pre-injury ambulation status at 1 year follow-up. Conclusion A standardized approach of less-invasive locked plating fixation and immediate unrestricted weight bearing appears safe and feasible in the management of this vulnerable patient cohort. Trial registration number This is a retrospective observational study without a Trial registration number.